Development of a Novel Class of Tubulin Inhibitor from Desmosdumotin B with a Hydroxylated Bicyclic B-Ring - Nakagawa-Goto, Kyoko (J Med Chem, 2015)
[Image: see text] A series of newly synthesized hydroxylated analogues of triethyldesmosdumotin B (TEDB) with a bicyclic B-ring exhibited a significantly different mode of action for affecting microtubule dynamics and spindle formation but had the same antiproliferative activity spectrum, including activity against multidrug-resistant tumors. These analogues efficiently induced cell cycle arrest at prometaphase and caused formation of immature multipolar spindles. 6′-Hydroxyl TEDB-TB (8) disrupted bipolar spindle formation but had a negligible effect on interphase microtubules. On the basis of the predicted binding modes of the new compounds with tubulin dimer, compound 4 forms three hydrogen bonds (H-bonds) only with α-tubulin at the colchicine site; in contrast, 8 forms H-bonds with both α- and β-tubulin. We predict that, when a compound/ligand, such as 8, forms H-bonds to both α- and β-tubulins, spindle formation is disrupted more than the dynamics of interphase microtubules. This result may reflect the well-known greater dynamicity of spindle microtubules as compared with interphase microtubules.